2022
DOI: 10.4093/dmj.2022.0070
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress and Dysregulated Autophagy in Human Pancreatic Beta Cells

Abstract: Pancreatic beta cell homeostasis is crucial for the synthesis and secretion of insulin; disruption of homeostasis causes diabetes, and is a treatment target. Adaptation to endoplasmic reticulum (ER) stress through the unfolded protein response (UPR) and adequate regulation of autophagy, which are closely linked, play essential roles in this homeostasis. In diabetes, the UPR and autophagy are dysregulated, which leads to beta cell failure and death. Various studies have explored methods to preserve pancreatic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…In diabetes-related toxic environments, including those with high glucose and NEFA levels, pancreatic β-cells are particularly exposed to heavy stresses because of their ability to produce and release insulin. Recently, regulation of the autophagy system has been considered to play a key role in overcoming stress [52]. In this context, we showed that DHA protects insulin-secreting cells against PA-induced apoptosis via autophagy activation and that this effect is mediated by GPR120 and specific mTOR phosphorylation on S2448.…”
Section: Discussionmentioning
confidence: 78%
“…In diabetes-related toxic environments, including those with high glucose and NEFA levels, pancreatic β-cells are particularly exposed to heavy stresses because of their ability to produce and release insulin. Recently, regulation of the autophagy system has been considered to play a key role in overcoming stress [52]. In this context, we showed that DHA protects insulin-secreting cells against PA-induced apoptosis via autophagy activation and that this effect is mediated by GPR120 and specific mTOR phosphorylation on S2448.…”
Section: Discussionmentioning
confidence: 78%
“…demonstrated that knocking down of EIF2AK3 in tissue or cells resulted in develop significant diabetes ( 32 ). In addition, EIF2AK3 has been recognized as an endoplasmic reticulum-related protein involved in β-cell death ( 33 ). These findings suggest that downregulated EIF2AK3 may induce the dysfunction of autophagy and β-cell death, therefore leading to T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays an important role in beta-cell homeostasis and survival (1). In fact, it has been extensively studied in the context of type 2 diabetes, beta-cell homeostasis (2), and ER stress response (43).…”
Section: Discussionmentioning
confidence: 99%